2023
DOI: 10.1039/d2na00625a
|View full text |Cite
|
Sign up to set email alerts
|

Advanced nanomaterials for modulating Alzheimer's related amyloid aggregation

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease that brings enormous economic pressure to families and society. The research found that inhibiting abnormal aggregation of Aβ and accelerating the dissociation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 280 publications
(508 reference statements)
0
7
0
Order By: Relevance
“…35 Moreover, AuNPs can provide enormous specific surface area to absorb the Aβ peptide. 28 MOFs are capable of adsorbing the Aβ peptide. However, MIL-100(Fe) showed slower adsorption behavior than MIL-101(Cr) NDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Moreover, AuNPs can provide enormous specific surface area to absorb the Aβ peptide. 28 MOFs are capable of adsorbing the Aβ peptide. However, MIL-100(Fe) showed slower adsorption behavior than MIL-101(Cr) NDC.…”
Section: Resultsmentioning
confidence: 99%
“…27 Moreover, AuNPs can provide enormous specific surface area to absorb the Ab peptide. 28 Recently, it has been confirmed that several MOFs are capable of adsorbing the Ab peptide. However, the adsorption capacity was found to vary between different MOFs.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the CPDs act as a stabilizing agent preventing the aggregation of MoS 2 nanosheets on CPDs. [48,49] Finally, the products are annealed at 700 °C to obtain MoS 2 @CPDs 3D nanoflower-like spheres. The morphology and structure characterization for CPDs is shown in Figures S1 and S2 (Supporting Information).…”
Section: Formation Of the Mos 2 @Cpds Nanoflowers Compositementioning
confidence: 99%
“…Carbon nanotubes (CNTs), another carbon-based nanoparticle, is a one-dimensional quantum material with a special structure made of graphene, which has the ability of drug delivery and therapy. 80 Recently, CNTs have been used for AD treatment through inhibiting amyloid fibrillation, disintegratingamyloid fibrils, and promoting the clearance of amyloid plaques. 81 They possess the ability to absorb various large and small biomolecules on their surface, which further inhibits amyloid fibrilization.…”
Section: Nanotechnology Mediated Drug Therapymentioning
confidence: 99%